2015
DOI: 10.17559/tv-20140228124615
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fundamental periods of reinforced shear wall dominant building models with empirical expressions

Abstract: Original scientific paper Empirical formulas for the estimation of the fundamental periods have been included in seismic codes, which mainly depend on building height, material (steel, reinforced concrete (RC)) and structural system type (frame, shear wall, etc.). These formulas have been usually derived from empirical data through regression analysis of the measured fundamental period of existing buildings subjected to seismic actions. A parametric study on 480 different RC building models with shear walls wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The evaluation was carried out with the formulas in ASCE 7-05 for steel and RC MRF, SW buildings, braced frames and other structural types. The differences between the periods from code formula and measured periods of low-to-medium rise buildings were relatively high [27].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The evaluation was carried out with the formulas in ASCE 7-05 for steel and RC MRF, SW buildings, braced frames and other structural types. The differences between the periods from code formula and measured periods of low-to-medium rise buildings were relatively high [27].…”
Section: Introductionmentioning
confidence: 90%
“…Lee and al. concluded that none of the code formulas examined in their study are sufficient for estimating the fundamental period of apartment buildings with shear wall system SW dominant systems [24]. Crowley and Pinho (2006) have proposed an empirical relationship between period T and height H "T = 0.1H" with a view to assess their validity for use in displacement-based structural assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, of two structures of the same stiffness, the heavier (greater mass) has a lower natural frequency and a longer natural period. This value can be obtained both with approximate formulas and as a result of numerical analysis [143][144][145][146]. The empirical relations and explanations stipulated in the corresponding design code for each country are given in Table 16.…”
Section: Comparison Of Natural Fundamental Periodsmentioning
confidence: 99%
“…Furthermore, reliable evaluation of the magnitude and effects of the fundamental vibration period for lateral resisting RC structures constitutes an essential step in estimating earthquake-induced forces and assessing their seismic response. The fundamental period of RC structures mainly depends on their mass and effective stiffness; consequently, it depends on their dimensions, morphology, and irregularities, among other factors that may affect their effective stiffness [17]. The period value of RC structures appears in formulas specified in most design codes to compute the design base-shear and resultant lateral forces.…”
Section: Hysteretic Stiffness and Fundamental Period Shiftmentioning
confidence: 99%